Development a Proposed System of Organization Structure to Management Multi Construction Projects (Journal of Engineering, 2014)
The purpose of this study is aimed to lay down an arranged platform suited to Iraqi constructional associations which in charge to carry out multi constructional projects, as it fulfilled management requirements and supervising, so that low - cost projects will be controlled in due term and quality. Based on primary info and observed data collected, the study thesis has been formulated in this way: Iraqi constructional sector bodies which are in charge to implement simultaneously multi constructional projects in need to reformulate its organized structure so that it will be more fitted to management and control of these projects. This thesis includes a theoretical part contained presenting the most important resources locally and internationally where it has direct relation with this study subject. Also it touches on the arrangement term and the kinds of organized structure of the multi constructional projects and control it. And its field part included in its first section studying the organized structure and functional arrangement practised in one of the Iraqi constructional projects. in charge of implemented simultaneously multi construction and exposing the defection of this arrangement. The second section of this study included reviewing the organized structure used by some of constructed corporations and foreign companies of implementing multi constructional projects .Thus, the deficiency points of the organized structure and the arrangement followed in Iraqi conduction sectors recognized and what it causes of control defections in the limitation of these projects. The deficiency points have been solved by developing a proposed system of the organized structure to administering and controlling of the multi constructional projects. The implementation of these projects have been controlled from its draw phase and passing the design phase and reference and implementation phase till the first deliver.